Prescribing Trends in Diabetic Neuropathy at a Tertiary Care Hospital - Banu, Parvin; Mondal, Subir; Biswas, Arunava; Naser, Syed Mohammed; Niyogi, Mausumi (Asian Journal of Medical Sciences, 2018)
Background: Neuropathy, being a common complication of diabetes mellitus is frequently encountered in patients related to duration and severity of hyperglycaemia and had a multi-modality treatment approach by the treating physicians. Aims and Objective: To understand and analyze the current drug prescribing trends in the management of diabetic neuropathy in hospitalized and OPD patients in a tertiary care hospital. Materials and Methods: A cross sectional, observational study on (n=100) patients of either sex aged between 18 to 70 years admitted in the Department of Neuromedicine as well as visiting the OPD was conducted for a period of 3 months. Prescriptions were collected and the relevant information i.e. drugs prescribed for diabetic neuropathy only excluding other drugs mentioned in the prescription were documented in a predesigned, pretested proforma and were analyzed. Results: All the prescribed drugs i.e. (100%) were oral formulations. The average number of drugs prescribed per prescription for the treatment of diabetic neuropathy including indoor and OPD patients was 3.60 ± 0.66. Prescription of single drug for the treatment of diabetic neuropathy was found to be the commonest trend among the prescribers i.e. 78% of all the prescriptions and they were all in their generic form. Conclusion: Gabapentin and pregablin (antiepileptics), amitryptylline (anti-depressants) and methylcobalamine were most commonly prescribed drugs. Side effects profiles of these drugs were also well evident among the patients. Much larger multicentric studies of similar type including private and public hospitals might reflect the true scenario of current drug prescribing trend among physicians in treating diabetic neuropathy. Asian Journal of Medical Sciences Vol.9(5) 2018 8-11